High-risk multiple myeloma predicted by circulating plasma cells and its genetic characteristics - Xia, Yuan; Shen, Na; Zhang, Run; Wu, Yujie; Shi, Qinglin; Li, Jianyong; Chen, Lijuan; Xu, Min; Jin, Yuanyuan (Frontiers in Oncology, 2023)
Circulating plasma cells (CPC) has been reported to be one of the indicators of high-risk multiple myeloma (MM), yet the prognostic significance of CPC in Chinese population and the genetic mechanisms underlying CPC formation has not been fully elucidated. In this investigation including 301 MM patients, we used multi-parameter flow cytometry (MFC) for CPC quantification and next-generation sequencing (NGS) technology for mutational landscape mapping. We demonstrated that CPC quantification could effectively mirror the tumor load, and CPC≥0.105% at diagnosis or detectable CPC after therapy indicates poor treatment response and adverse outcome, and the introduction of CPC into the R-ISS enables a more accurate risk stratification. Interestingly, we noticed an elevated percentage of light-chain MM in patients with higher CPC. Mutational landscape revealed that patients harboring mutations in TP53, BRAF, DNMT3A, TENT5C and IL-6/JAK/STAT3 pathway related genes tended to have higher CPC levels. Gene enrichment analysis demonstrated that pathways involving chromosome regulation and adhesion may be potential mechanisms accounting for CPC formation. Accordingly, quantification of CPC may provide a less-invasive and reliable approach for identifying high-risk MM in Chinese population.